Analisis Laporan Arus Kas Untuk Menilai Kinerja Keuangan PT Mayora Indah Tbk di Bursa Efek Indonesia - Alfitriyani, Nendra Ressa; Jefri, Riny (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
This study aims to analyze the cash flow performance of PT Mayora Indah Tbk using four key ratios, namely CFO/CL, CFO/TD, CFO/CapEx, and CFO/NI, to assess liquidity, solvency, investment efficiency, and earnings quality during the 2021 to 2024 period. The research employs a quantitative descriptive method using secondary data from the company’s cash flow statements published by the Indonesia Stock Exchange. The analysis includes calculating each annual ratio, identifying trends, and interpreting the results based on cash flow theory and the company’s financial conditions. The findings indicate increasing CFO, improving liquidity and solvency ratios, and consistent investment funding capacity supported by internal cash. The CFO/NI ratio remains above one, although showing a slight decline, suggesting that earnings quality is still strong but requires further monitoring. Overall, the cash flow analysis highlights the company’s ability to maintain operational cash stability, meet financial obligations, and support long term investment needs.